Morphological and Behavioral Impact of AAV2/5-Mediated Overexpression of Human Wildtype Alpha-Synuclein in the Rat Nigrostriatal System - Gombash, Sara E.; Manfredsson, Fredric P.; Kemp, Christopher J.; Kuhn, Nathan C.; Fleming, Sheila M.; Egan, Ann E.; Grant, Laura M.; Ciucci, Michelle R.; MacKeigan, Jeffrey P.; Sortwell, Caryl E. (PloS one, 2013)
The discovery of the involvement of alpha-synuclein (α-syn) in Parkinson's disease (PD) pathogenesis has resulted in the development and use of viral vector-mediated α-syn overexpression rodent models. The goal of these series of experiments was to characterize the neurodegeneration and functional deficits resulting from injection of recombinant adeno-associated virus (rAAV) serotype 2/5-expressing human wildtype α-syn in the rat substantia nigra (SN). Rats were unilaterally injected into two sites in the SN with either rAAV2/5-expressing green fluorescent protein (GFP, 1.2 x 10(13)) or varying titers (2.2 x 10(12), 1.0 x 10(13), 5.9 x 10(13), or 1.0 x 10(14)) of rAAV2/5-α-syn. Cohorts of rats were euthanized 4, 8, or 12 weeks following vector injection. The severity of tyrosine hydroxylase immunoreactive (THir) neuron death in the SN pars compacta (SNpc) was dependent on vector titer. An identical magnitude of nigrostriatal degeneration (60-70% SNpc THir neuron degeneration and 40-50% loss of striatal TH expression) was observed four weeks following 1.0 x 10(14) titer rAAV2/5-α-syn injection and 8 weeks following 1.0 x 10(13) titer rAAV2/5-α-syn injection. THir neuron degeneration was relatively uniform throughout the rostral-caudal axis of the SNpc. Despite equivalent nigrostriatal degeneration between the 1.0 x 10(13) and 1.0 x 10(14) rAAV2/5-α-syn groups, functional impairment in the cylinder test and the adjusting steps task was only observed in rats with the longer 8 week duration of α-syn expression. Motor impairment in the cylinder task was highly correlated to striatal TH loss. Further, 8 weeks following 5.9 x 10(13) rAAV2/5-α-syn injection deficits in ultrasonic vocalizations were observed. In conclusion, our rAAV2/5-α-syn overexpression model demonstrates robust nigrostriatal α-syn overexpression, induces significant nigrostriatal degeneration that is both vector and duration dependent and under specific parameters can result in motor impairment that directly relates to the level of striatal TH denervation.